Designing fluorescent probes for the study of intracellular cholesterol metabolism - Hintikka, Jukka (2019)
Cholesterol is abundantly present in animal cells. It comprises a major portion of the lipids in mammalian cell membranes and is required for the synthesis of steroid hormones, lipoproteins and bile acids. Many characteristics of cellular membranes are highly affected by their cholesterol content. The intracellular transport and distribution of cholesterol is affected and controlled by many distinct and individual mechanisms, many of which are not fully understood. Fluorescent sterols or sterol-binding molecules are commonly utilized as probes to provide valuable data on cholesterol transport and distribution. Three new synthetic fluorophores, Fp1-Fp3, were provided by the Institute of Biotechnology of the Czech Academy of Sciences. Their applicability in the fluorophore-labeling of cholic acid and methyl lithocholate was investigated. A conjugate of Fp2 and cholic acid was successfully synthesized (yield 14 %) for further molecular biology studies.